Response Surface Methodology for Formulating PVA/Starch/Lignin Biodegradable Plastic - Ratnawati Ratnawati; Retno Wulandari; Andri Cahyo Kumoro; Hadiyanto Hadiyanto (Ital Publication, 2022)
The use of petroleum-based plastics has raised environmental issues as more plastic waste enters and accumulates in the environment. It has led to the development of biodegradable plastics. Starch is one of the potential materials to make biodegradable plastic, but starch-based plastic has poor mechanical strength. Blending starch with poly(vinyl alcohol) (PVA) and lignin is expected to improve the mechanical properties of the plastic. Biodegradable plastic films from PVA/starch/lignin blends with glycerol as a plasticizer were prepared using an internal mixer for compounding and a hot press molding machine for film making. The percentage of lignin (2-10%), glycerol (25-65%), and mixing temperature (190-230 oC) were varied according to the three levels of the Box-Behnken design. The ANOVA evaluation revealed that glycerol had the most significant effect on the mechanical properties of the film. Then, three models for the estimation of tensile strength, elongation at break, and tear resistance were developed. As expected, the models satisfactorily predict the effect of all input variables on the response variables. The optimum conditions for preparing the film were acquired from the equations, namely 197.6 oC for the temperature, 10% for lignin, and 45.1% for glycerol. The biodegradable plastic prepared using the optimum conditions possessed a tensile strength of 8.46 ± 1.08 MPa, an elongation at break of 139.00 ± 8.59%, and a tear resistance of 69.50 ± 2.50 N/mm. These values are in good agreement with the predicted values. Doi: 10.28991/ESJ-2022-06-02-03 Full Text: PDF